Subtle Cognitive Deficits in Adults With a Previous History of Sydenham's Chorea During Childhood - Cavalcanti, Andre; Hilario, Maria Odete E.; Santos, Flávia Heloísa dos [UNESP]; Prado Bolognani, Silvia Adriana; Amodeo Bueno, Orlando Francisco; Len, Claudio Arnaldo (Wiley-liss, 2010)
Objective. To evaluate the neuropsychological profile and health-related quality of life (HRQOL) of adults who had rheumatic fever (RF) during childhood with and without Sydenham's chorea (SC).Methods. Three groups of patients were assessed: adults who had RF with SC during childhood (SC group), adults who had RF without SC during childhood (RF group), and controls (CT group). A range of neuropsychological tests looked at several cognitive domains. HRQOL was measured through a Brazilian version of the Short Form 36 (SF-36) health survey.Results. Twenty patients were included in the SC group, 23 patients in the RF group, and 19 patients in the CT group. The 3 groups were homogeneous regarding sex (P = 0.078), age (P = 0.799), schooling (P = 0.600), socioeconomic status (P = 0.138), intelligence quotient (P = 0.329), and scores for anxiety (P = 0.156) and depression (P = 0.076). The SC group demonstrated inferior performance in tests that assessed attention (Digit Span Forward [ P = 0.005], Corsi Block Forward [ P = 0.014]), speeded information processing (Trail Making A [ P = 0.009], Symbol Search [ P = 0.042]), and executive functions and working memory (Corsi Block Backward [ P = 0.028]), and higher scores for attention deficit scale (P = 0.030) when compared with the RF and CT groups. They also showed a tendency toward lower scores in the physical aspects, vitality, emotional aspects, and mental health domains of the SF-36. The RF group had a lower score for the general health domain than the CT group (P = 0.030).Conclusion. Patients who had SC during childhood can exhibit inferior performance in tasks that evaluate attention, speeded information processing, executive functions, and working memory in adult life. Therefore, there is indirect evidence of the persistence of dysfunction in cerebral circuits involved with the basal ganglia. They also presented a worse self-evaluation in HRQOL that was not related to cognitive impairments.